Identification of MAEL as a promoter for the drug resistance model of iPSCs derived from T‐ALL. (29th April 2022) - Chen, Xuemei; Wen, Feiqiu; Li, Zhu; Li, Weiran; Zhou, Meiling; Sun, Xizhuo; Zhao, Pan; Zou, Chang; Liu, Tao
Abstract: Significant progress has been made in the diagnosis and treatment of the drug‐resistant and highly recurrent refractory T cell acute lymphoblastic leukemia (T‐ALL). Primary tumor cell‐derived induced pluripotent stem cells (iPSCs) have become very useful tumor models for cancer research including drug sensitivity tests. In the present study, we investigated the mechanism underlying drug resistance in T‐ALL using the T‐ALL‐derived iPSCs (T‐iPSCs) model. T‐ALL cells were transformed using iPSC reprogramming factors (Sox‐2, Klf4, Oct4, and Myc) via nonintegrating Sendai virus. T‐iPSCs with the Notch1 mutation were then identified through genomic sequencing. Furthermore, T‐iPSCs resistant to 80 μM LY411575, a γ‐secretase and Notch signal inhibitor, were also established. We found a significant difference in the expression of drug resistance‐related genes between the drug‐resistant T‐iPSCs and drug‐sensitive groups. Among the 27 genes, six most differently expressed genes (DEGs) based on Log2 FC >5 were identified. Knockdown analyses using RNA interference (RNAi) revealed that MAEL is the most important gene associated with drug resistance in T‐ALL cells. Also, MAEL knockdown downregulated expression of MRP and LRP in drug‐resistant T‐iPSCs. Interestingly, this phenomenon partially restored the sensitivity of the cells to LY411575. Furthermore, overexpression of the MAEL gene enhanced drug resistance against LY411575. Conclusively, MAEL promotes LY411575 resistance in T‐ALL cells increasing the expression of MRP and LRP genes. Abstract : Our study investigated the mechanism underlying drug resistance in T‐ALL using the T‐ALL derived iPSCs (T‐iPSCs) model. We found that overexpression of MAEL promotes drug resistance in T‐ALL by increasing the expression of drug resistance‐related genes. Accordingly, MAEL is potentially a new treatment target for drug‐resistant T‐ALL.